Factors That Shape Mosque Archives A Multi-level Model - Müssig, Stephanie (Journal of Muslims in Europe, 2022)
In most mosque archives, the subject range seems to be limited to bureaucratic matters. In this article I discuss the factors that are responsible for this constraint. Using academic literature on (Christian) religious and (ethnic) community archives, as well as relying on the research presented in this special issue, I develop a hierarchical (or multi-level) model of subject ranges in mosque archives by considering factors at the individual, intermediate, and system level. I argue that the individual dispositions of mosque leaders regarding resources and attitudes, as well as funds at the intermediate level, are key to the maturing of the archiving culture in mosques.
Created from Fastlane, Scopus look-up
Keywords: archives; mosque; resources; subject range